Studi Perilaku Individu Di Lingkungan Akademik Universitas Katolik Widya Karya Malang - Andy Endra Krisna (EBISMAN eBisnis Manajemen, 2024)
This research aims to explain various aspects of human behavior in an organization. This includes the influence of organizations on individuals and how individuals impact organizations. Literature study was used in this research. This study uses descriptive-qualitative as its approach. The results of this research show that individual behavior influenced by the organization. The organization reffered to here is Widya Karya Catholic University of Malang., It is influenced by internal and external factors. Yet individual behavior is influenced also by psychological, physiological and environmental factors. Thus, a manager must understand a person's innate characteristics well, such as his biography, personality, nature of perception, and also his attitude in order to then optimize his role in the organization he leads.